2022
DOI: 10.26434/chemrxiv-2022-xwbst
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Encoding Hierarchical 3D Architecture through Inverse Design of Programmable Bonds

Abstract: The ability to fabricate materials and devices by-design at small scales, largely based in advances in lithographic and additive manufacturing methods, has led to the tremendous technological progress of the last decades. However, the growing need to structure 3D nanoscale matter for emergent functions, according to design and in a massively parallel manner, requires new means of material fabrication. Here, we demonstrate the concept and experimental realization of the encoded assembly of nanoparticles into pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…1D ). Using sticky-end hybridization allows us to encode many low cross-talk interactions ( 15 , 35 , 37 39 ) without changing any internal routing of the DNA origami, which could otherwise have unintended effects on the monomer structure ( 19 , 20 , 40 ). Last, we assemble tubules at a constant temperature chosen such that the intersubunit interactions are weak and reversible (section S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1D ). Using sticky-end hybridization allows us to encode many low cross-talk interactions ( 15 , 35 , 37 39 ) without changing any internal routing of the DNA origami, which could otherwise have unintended effects on the monomer structure ( 19 , 20 , 40 ). Last, we assemble tubules at a constant temperature chosen such that the intersubunit interactions are weak and reversible (section S1).…”
Section: Resultsmentioning
confidence: 99%
“…More complex geometries, such as capsids or gyroids, require considering local point symmetries of the structure ( 16 , 19 , 43 , 45 ) to encode the correct interactions, while fully addressable clusters often reveal their allowed colorings through detailed searches of all possible interactions ( 46 ). Recent efforts have also shown that colorings can be used to encode hierarchical structures into crystalline self-assemblies ( 15 ). As assembly structures become more complex, finding the right scheme to encode large libraries of interactions may require new methods, such as SAT-assembly ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assemble tilings with up to 12 species, containing as many as 72 triangles in a unit cell, significantly larger than other recent examples reported in the literature. 34 Finally, by conjugating DNAgrafted gold nanoparticles onto a small number of species, we fabricate various gold nanoparticle supracrystals with periodicities reaching hundreds of nanometers (Figure 1D,E). Fourier transforms of the gold nanoparticles exhibit distinct low-spatial-frequency features, demonstrating order on length scales larger than the gold nanoparticles themselves.…”
mentioning
confidence: 99%
“…To show that our design scheme works in practice, we synthesize DNA origami subunits with programmable interactions (Figure A). We assemble tilings with up to 12 species, containing as many as 72 triangles in a unit cell, significantly larger than other recent examples reported in the literature . Finally, by conjugating DNA-grafted gold nanoparticles onto a small number of species, we fabricate various gold nanoparticle supracrystals with periodicities reaching hundreds of nanometers (Figure D,E).…”
mentioning
confidence: 99%